Editorial: challenges and opportunities for services marketers in a culturally diverse global marketplace - Sharma, Piyush; Tam, J.; Wu, Z. (Routledge, 2018)
Purpose: The purpose of this special issue is to extend the growing research on the challenges and opportunities facing services marketers in an increasingly culturally diverse global marketplace. Design/methodology/approach: The nine papers included in this special issue use a variety of research methods (e.g. case study, experiments and surveys), participants (e.g. customers, employees and online panel members) and service settings (e.g. fast food, post office, weight loss, bank, home loan, personal fitness and offshore outsourcing). Findings: All the nine papers highlight the importance of studying the unique perspectives of the customers and employees involved in intercultural interactions in diverse service settings in marketplaces and societies that are either already or have recently become multicultural. Research limitations/implications: The findings from the nine papers have useful implications for future research on services marketing in multicultural markets, although these may not always be generalisable beyond the unique context of the studies reported in each of these papers. Practical implications: All the nine papers also present some useful directions for services marketing managers in the multicultural markets, to help them understand and manage the expectations of their culturally diverse customers, as well as employees. Originality/value: This special issue is unique because it is one of the first attempts to understand the unique challenges and opportunities for services marketers in the growing multicultural global marketplace, from a theoretical, as well as empirical, point of view.